Temporal effect of ammonium sulfate on soil nitrogen content, growth and yield of oil palm cultivated on Alan Forest Tropical Peat, Sarawak, Malaysia - Siaw, Ting Chuan (2016)
Tropical peatland is the last frontier of arable land available for agricultural development in Sarawak, Malaysia.There are three main types of forests in Sarawak; mixed peat swamp, alan bunga/batu and padang paya. The study of suitable nitrogen rates are limited in Alan bunga forest for good oil palm yield. The purpose of this study is to determine the growth response of oil palm on alan bunga tropical peat to different N fertilizer application rates on total N and available N in the soil, leaf N concentration, vegetative growth and oil palm yield. A study was carried out from 2010 to 2012 at an oil palm plantation in Sibu, Sarawak, Malaysia. The experiment was laid out in a randomized complete block design (RCBD) with three replications. The six-year-old mature palms were planted in a triangular pattern with a planting distance of 8.5 × 8.5 × 8.5 m. Ammonium sulphate (AS) was used as N source with four different rates: 0 kg nitrogen (N1), 0.21kg nitrogen (N2), 0.42 kg nitrogen (N3) and 0.84 kg nitrogen (N4)/palm/year. In the first objective, the effect of N fertilizer rates on soil total N is significant at 0 - 25 cm (P = 0.012) and 25 - 50 cm (P = 0.041). Results for NH4 + showed that there were no significant interactions between time and N fertilizer rates (P = 0.25; P = 0.58) at both soil depths. For NO3 -, only 0 – 25 cm (P = 0.041) displayed significant interactions effect. This indicates that NO3 - responses over time were different among treatments in which N2 and N3 contributed to the change. Effect of different N fertilizer rates on leaf N concentration illustrates that only time effect was significant (P = 1.762x10-5). There were no statistically significant effects of different N fertilizer towards LAI (P = 0.14) and frond dry weight (P = 0.19). However, there were statistically significant for time (P =7.412x10-8) and (P=2.378x10-8) towards both of them. Association between time and treatments (P = 0.62; P = 0.29) were not significant in both LAI and frond dry weight. Analysis for palm yield reveal that different level of N fertilizer application did not have any significant effect on either bunch number or FFB (P = 0.26 and P = 0.31). However, the effect of N fertilizer rates on FFB and bunch number can be seen through the association with time (P = 0.006) and (P = 0.029). The significant quadratic trend shown by N4 indicates that N4 produced the most FFB within the shortest time.